An fMRI Study Dissociating Distance Measures Computed by Broca’s Area in Movement Processing: Clause boundary vs Identity - Santi, Andrea; Friederici, Angela D.; Makuuchi, Michiru; Grodzinsky, Yosef (Frontiers in Psychology, 2015)
Behavioral studies of sentence comprehension suggest that processing long-distance dependencies is subject to interference effects when Noun Phrases (NP) similar to the dependency head intervene the dependency. Neuroimaging studies converge in localizing such effects to Broca’s area, showing that activity in Broca’s area increases with the number of NP interveners crossed by a moved NP of the same type. To test if NP interference effects are modulated by adding an intervening clause boundary, which should by hypothesis increase the number of successive-cyclic movements, we conducted an fMRI study contrasting NP interveners with clausal (CP) interveners. Our design thus had two components: (I) the number of NP interveners crossed by movement was parametrically modulated; (II) CP-intervention was contrasted with NP-intervention. The number of NP interveners parametrically modulated a cluster straddling left BA44/45 of Broca’s area, replicating earlier studies. Adding an intervening clause boundary did not significantly modulate the size of the NP interference effect in Broca’s area. Yet, such an interaction effect was observed in the Superior Frontal Gyrus (SFG). Therefore, the involvement of Broca’s area in processing syntactic movement is best captured by memory mechanisms affected by a grammatically instantiated type-identity (ie, NP) intervention.